Consensus Ad Idem: A Plea for Objectivity in Telephonic Contracts - Kumar, D Ganesh; Gudinho, Akshay Douglas (Christ University Law Journal, 2021)
Consensus Ad Idem, legally defined as „meeting of minds‟, at the time of the formation of a contract, warrants a cardinal jurisprudential question which transcends its mere literal meaning. In Indian Contract Law, the trend has followed the test of objectivity, whereby it is not the actual intent of the party or parties that enter into the contract that is the subject of judicial evaluation, but it is what a reasonable man would deliberate in the peculiar circumstances of the case. However, the evaluation of telephonic conversations merit intrinsic jurisprudential insight. While applying the objective test, the questions that arise are - is there legal certainty of assent to a contract over telephonic conversations i.e. whether there is free consent. Do the parties have the capacity to contract over telephone? What are the liabilities of the telephone operator and his legal bond to the contract between two or more contracting parties? Does it amount to violation of the fundamental rights to freedom of speech and expression and the right to privacy? The authors attempt to provide an objective analysis of communication in contracts over telephonic means and the constitutional environment embedded therein. To this end, a plea for due diligence prior to the formation of telephonic contracts shall be made in order to bring objectivity to the judicial evaluation of telephonic contracts.